INTERACTION OF TEMPERATURE AND EXTRACTION TIME ON THE RENDEMENT AND SOME PROPERTIES OF LIME PECTIN (CITRUS AURANTIFOLIA S) - Lumuindong, Frans; Mamuaja, Christine F (Journal of Agriculture, 2022)
This study aims to determine the right temperature and extraction time to get the best yield and quality of pectin from lime peel. It is hoped that the results of this study can become a reference for studying and utilizing lime peels as a pectin producer. This research was carried out at the Food Technology Laboratory, Faculty of Agriculture, University of Sam Ratulangi. This study used a completely randomized design (RAL) with 2 factors, namely extraction temperature (60, 70, and 900C) and extraction time (40, 60, 80, and 100 minutes) with 3 replications. The results showed that the yield of orange peel pectin lime ranged from 3.1826% to 5.2211% wet weight. The highest yield of pectin was produced and the extraction temperature was treated at 900C for 100 minutes. The methoxy content ranges from 7.1706% to 8.3534% so that it is classified as a high methoxyl content pectin, the pectin water content ranges from 9.734% to 13.7703% while the ash content ranges from 1.8009% to 2.5339%. From these results it was concluded that the best conditions for extracting lime peel pectin were at 900C with an extraction time of 100 minutes and lime peels could be used for commercial processing of pectin.